Impact of sex on humoral immunity with live influenza B virus vaccines in mice - Stivalis Cardenas-Garcia; C. Joaquín Cáceres; Aarti Jain; Ginger Geiger; Jong-Suk Mo; L. Claire Gay; Brittany Seibert; Algimantas Jasinskas; Rie Nakajima; Daniela S. Rajao; D. Huw Davies; Daniel R. Perez (npj Vaccines, 2024)
Abstract Influenza B virus (FLUBV) poses a significant infectious threat, with frequent vaccine mismatch limiting its effectiveness. Our previous work investigated the safety and efficacy of modified live attenuated FLUBV vaccines with rearranged genomes (FluB-RAM and FluB-RANS) or a temperature-sensitive PB1 segment with a C-terminal HA tag (FluB-att). In this study, we compared the immune responses of female and male DBA/2J mice vaccinated with these vaccines, including versions containing a chimeric HA segment with an N-terminal IgA-inducing peptide (IGIP). Importantly, both recombinant viruses with and without IGIP remained genetically stable during egg passage. We found that introducing IGIP strengthened vaccine attenuation, particularly for FluB-RAM/IGIP. Prime-boost vaccination completely protected mice against lethal challenge with a homologous FLUBV strain. Notably, recombinant viruses induced robust neutralizing antibody responses (hemagglutination inhibition titers ≥40) alongside antibodies against NA and NP. Interestingly, female mice displayed a consistent trend of enhanced humoral and cross-reactive IgG and IgA responses against HA, NA, and NP compared to male counterparts, regardless of the vaccine used. However, the presence of IGIP generally led to lower anti-HA responses but higher anti-NA and anti-NP responses, particularly of the IgA isotype. These trends were further reflected in mucosal and serological responses two weeks after challenge, with clear distinctions based on sex, vaccine backbone, and IGIP inclusion. These findings hold significant promise for advancing the development of universal influenza vaccines.